Consequences and Institutional Determinants of Unregulated Corporate Financial Statements: Evidence from Embedded Value Reporting - SERAFEIM, GEORGE (Journal of Accounting Research, 2011)
ABSTRACT I analyze Embedded Value (EV) reporting by firms with life insurance operations to assess the impact of unregulated financial reporting on transparency and to examine the institutional characteristics that promote unregulated reporting. Under EV accounting, the present value of future cash flows from in‐force contracts is included in shareholders’ equity, and profit is calculated as the change in equity between two periods. In contrast to Generally Accepted Accounting Principles (GAAP), this approach produces higher shareholder's equity and recognizes income at contract inception. I find firms that adopt EV reporting exhibit a decline in information asymmetry, with the decline increasing as EV reporting evolves to address methodological deficiencies and to permit more comparability across firms. The decrease in information asymmetry is contingent on providing an audit certification, and larger for firms that commit to providing EV reports. Moreover, I document that EV reporting is more widespread in countries with more hostile takeovers, managers that do not avoid volatile income measures, regulators that are less likely to intervene in the product market, and analysts that believe EV disclosure increases the value of their information intermediation function.